Association between pretreatment lymphocyte count and response to PD1 inhibitors in head and neck squamous cell carcinomas. Issue 1 (31st August 2018) - Ho, Won Jin; Yarchoan, Mark; Hopkins, Alex; Mehra, Ranee; Grossman, Stuart; Kang, Hyunseok
Abstract : Background: Low absolute lymphocyte count (ALC) has previously been established as a marker of poor prognosis in multiple cancer types. There is growing evidence that ALC may also be associated with response to immunotherapy. This study explores whether response to PD1 inhibitors in recurrent and/or metastatic head and neck squamous cell carcinoma (R/M HNSCC) is associated with pretreatment ALC. Methods: Thirty-four R/M HNSCC patients who received either nivolumab or pembrolizumab between January 2014 and May 2018 at Johns Hopkins were identified retrospectively. Pretreatment blood counts in patients with and without clinical benefit from PD1 inhibitors were compared. Time-to-progression analyses were performed by dichotomizing the study cohort with the threshold of ALC 600 cells/μl, which is approximately 1.5 standard deviations away from treatment-naïve baseline mean. Results: Patients with lower ALC appeared to have significantly less clinical benefit from anti-PD1 therapy. Those patients with pretreatment ALC < 600 cells/μl also had shorter PFS than patients with pretreatment ALC ≥ 600 cells/μl (median PFS 60 days vs. 141 days, p  < 0.05). These results were consistent with multivariate proportional hazards analyses demonstrating significant association with progression. These observations were further supported by an expansion cohort analysis incorporating additional fourteen R/M HNSCC patients who received other checkpoint immunotherapy regimens at our institution. Conclusions: This study for the first time demonstrates that pretreatment ALC is significantly associated with response to PD1 inhibitors in R/M HNSCC patients.